Formaţiuni politice şi activitate parlamentară. O perspectivă longitudinală asupra grupului parlamentar al Uniunii Democrate a Maghiarilor din România (Political Parties and Parliamentary Activity. A Case study on the Democratic Alliance of Hungarians in Romania) - Bogdan GHEORGHIŢĂ; Dragoş DRAGOMAN; Sabina-Adina LUCA (Polis: Revista de Stiinte Politice, 2013)
The political representation of the ethnic groups is important for the stability of a political system. Observing the parliamentary activity of the Democratic Alliance of Hungarians in Romania (DAHR), between 1990-2012, we have tried to understand the differences between political parties in parliament. It seems that DAHR is rather characterised by a political „apathy” having few legislative initiatives. Also, this political group seems to be rather a conservative organisation, if we consider that there are few new members wich enter as deputies or senators over the time. An explanation could be, that they are more concerned with the fullfilment of targets like the introduction of mother tongue education.